Dari Taman Ke Kota: Merekonstruksi Wahyu 21-22 Sebagai Pembaruan, Bukan Pelarian Kosmik - Ariwandira Pratama Siagian (STT IKSM SANTOSA ASIH, 2026)
This study seeks to reconstruct the interpretation of Revelation 21–22 by emphasizing that Christian eschatology is not a form of cosmic escape from the world, but rather the comprehensive renewal of creation. Employing a theological hermeneutic approach and biblical-narrative analysis, the text is read in continuity with the garden motif in Genesis, culminating in the vision of the New Jerusalem as a city. The findings indicate that the transformation from garden to city is not merely symbolic, but reflects God’s vision of an integrated reality where nature, culture, and human life are fully restored. The city in Revelation does not abolish the old world; instead, it renews it into a sacred, just, and God-filled space. Therefore, Christian eschatology carries ethical and practical implications, encouraging active engagement in social, ecological, and cultural transformation in the present world. This perspective rejects dualism that separates the spiritual from the material and affirms that God’s future is rooted in the renewal of creation rather than its destruction.